2020
DOI: 10.47277/ijcncs/8(5)1
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach of Threat Hunting Using Memory Forensics

Abstract: The capacity and occurrence of new cyber-attacks have shattered in recent years. Such measures have very complicated workflows and comprise multiple illegal actors and organizations. Threat hunting demonstrates the process of proactively searching through networks for threats based on zero-day attacks by repeating the hunting process again and again. Unlike threat intelligence, it uses different automated security tools to collect logs in order to provide a pattern for making new intelligence-based tools by fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Because of the limitation of knowledge retrievals, the researchers focus on "nonblack-box classifiers, including random forest and decision trees approach. e literature of [104,[129][130][131][132] examined the decision forest and decision tree, and they reported that decision forest classifiers were more effective than implementing a decision tree for its overfitting issues. An algorithm extracts the rules from 86% 88% 90% 90% 91% 91% 92% 92% 93% 94% 95% training data using a decision tree that generates either a limited or a single set of logic rules (for example, whenever C2 entropy value is less than 101.01, class value � seizure) and stops growing the tree by adding more records to the training dataset once the rule is accepted by the algorithm [127].…”
Section: Nonblack-box Classifiers In Seizure Detectionmentioning
confidence: 99%
“…Because of the limitation of knowledge retrievals, the researchers focus on "nonblack-box classifiers, including random forest and decision trees approach. e literature of [104,[129][130][131][132] examined the decision forest and decision tree, and they reported that decision forest classifiers were more effective than implementing a decision tree for its overfitting issues. An algorithm extracts the rules from 86% 88% 90% 90% 91% 91% 92% 92% 93% 94% 95% training data using a decision tree that generates either a limited or a single set of logic rules (for example, whenever C2 entropy value is less than 101.01, class value � seizure) and stops growing the tree by adding more records to the training dataset once the rule is accepted by the algorithm [127].…”
Section: Nonblack-box Classifiers In Seizure Detectionmentioning
confidence: 99%
“…Logs in the memory are an important place to investigate for attacks. Automated security tools formulate logs to organize the patterns used to make new tools [179]. The authors of [179] explained that some design tools are limited in the ways they collect the logs.…”
Section: Memorymentioning
confidence: 99%
“…Automated security tools formulate logs to organize the patterns used to make new tools [179]. The authors of [179] explained that some design tools are limited in the ways they collect the logs. To create valuable logs researchers have proposed generating malicious code alerts and binding memory forensic processes for active threat hunting [179].…”
Section: Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…[6]. These ARP spoofing can be sectioned into two rudimentary types namely deceitful the host and deceitful the gateway of the interior network [7]. When a user desires to interconnect with another user belonging to the similar network with unidentified MAC address, it results in a broadcast where ARP request in the network.…”
Section: Arp Cache Of 'D' Arp Cache Of 'M'mentioning
confidence: 99%